Pengaruh Ideologi Maskulin Dan Harga Diri Terhadap Konflik Peran Gender Pada Mahasiswa Laki-Laki Yang Melanjutkan Studi Keperawatan - Sagala, Voriska Agnestasia; Brahmana, Karina Meriem Beru (Institut Agama Kristen Negeri Tarutung, 2025)
This study aims to examine the influence of masculine ideology and self-esteem on gender role conflict among male nursing students. The research employed a quantitative approach using multiple linear regression analysis. The instruments used included the Male Role Norms Scale (MRNS), Rosenberg Self-Esteem Scale (RSES), and Gender Role Conflict Scale (GRCS). The findings revealed that masculine ideology had a significant effect on gender role conflict (p 0.05) with a contribution of 30%. Meanwhile, self-esteem did not show a statistically significant effect, although it had a positive correlation direction. The study found that male nursing students possess high masculine ideology and self-esteem, yet still experience high levels of gender role conflict. These results suggest that traditional masculinity values play a dominant role in shaping gender identity pressures, particularly in professions considered feminine. The study recommends the development of gender-sensitive educational approaches to reduce psychological stress and promote greater social acceptance of non-traditional gender roles.